Unidades Taxonômicas Operacionais Moleculares (MOTUs) identificadas dentro do gênero Alouatta Lacèpéde, 1799 (Atelidae, Primates) por abordagens de delimitação de espécies single-gene (mtDNA) - Ávila, Luana Portela Faria e (2022)
The howler monkeys or guaribas are Neotropical primates belonging to the genus Alouatta Lacèpéde, 1799 (Atelidae, Primates) that have a wide distribution in the Americas, occurring in the Mesoamerica and South America. Taxonomic reviews point to the existence of five to 14 species in the genus and phylogenetic relationships among them are not yet fully resolved. DNA barcoding, and the associated single-gene species delimitation approaches, have allowed the study of inter and intraspecific genetic diversity and provided data for delimiting Molecular Operational Taxonomic Units (MOTUs). The present study aimed to assess whether the MOTUs recovered within the genus Alouatta are consistent with current taxonomic proposals for howler monkeys in Brazil. Our study included samples from several localities in Brazil of the following taxa: A. pigra, A. palliata (A. p. mexicana, A. p. coibensis, A. p. trabeata, A. p. aequatorialis), A. belzebul (A. b. discolor, A. b. ululata); A. caraya; A. guariba (A. g. clamitans); A. seniculus (A. s. juara, A. s. puruensis, A. sara); A. macconnelli e A. nigerrima. We analyzed two regions of the mitochondrial genome, Cytochrome Oxidase B (Cyt b) and Cytochrome Oxidase subunit I (COI). We analyzed 339 sequences for Cyt bwith 138 of them produced in this study and 201 obtained from GenBank (https://www.ncbi.nlm.nih.gov/genbank/). For COI, we analyzed a total of 98 sequences, among which 82 were generated in this study and 16 were obtained from GenBank. To delimit MOTUs, we analyzed Cyt b and COI data independently by adopting (1) genetic distance-based delimitation approaches (jMOTU and ASAP) using the Kimura 2-parameter model (K2P) and calculating the optimal threshold (OT); and (2) approaches based on coalescence and phylogeny (PTP, bPTP, GMYC). The distance approach pointed to 1.34% and 1.11% as optimal thresholds between intraspecific variation for COI and Cyt b regions, respectively. Our results delimited 12 MOTUs within the genus Alouatta that correspond to taxonomic entities proposed by different systematic reviews, as follows: MOTU-pigra (A. pigra), MOTU-palliata (A. palliata, including all subspecies), MOTU-caraya (A. caraya), MOTU-seniculus 1 (A. sara and A. s. puruensis), MOTU-seniculus 2 (A. seniculus and A. s. juara), MOTU-macconnelli (A. macconnelli), MOTU-nigerrima (A. nigerrima), MOTU-belzebul 1 (A. discolor), MOTU-belzebul 2 (A. belzebul and A. b. ululata), MOTU-guariba 1, MOTU-guariba 2, MOTU-guariba 3. The three MOTUs for the southern-southeastern Atlantic Forest howler monkeys (A. guariba) distinguish those from RJ and MG as MOTU-guariba 1 (A. clamitans 1), those from ES, MG and BA as MOTU-guariba 2 (A. guariba) and those from SC as MOTU-guariba 3 (A. clamitans 2). Specimens from SP showed a paraphyletic arrangement in the three MOTUs, which may indicate the presence of ancestral polymorphism, hybridization, or be interpreted as a possible contact or migration zone that received animals from distinct lineages. Our data identified at least two independent evolutionary lineages for the A. guariba, A. seniculus and A. belzebul complexes, suggesting taxonomic inconsistencies. However, for A. nigerrima the Cyt b analyses recovered this species inside MOTU-macconnelli, the coalescence phylogenetic analyses show a unique and exclusive group with a high support value (PP>0.9). On the other hand, this species has an allopatric distribution, and their traditional taxonomic classification is recognized as valid. Thus, we consider it a distinct MOTU from MOTU-macconnelli, with recent divergence, but emphasize the importance of extending the sampling of this taxon, and performing complementary analyses, including other regions of the genome.